The Use of Bulk-Fill Flow in the Customization of Glass Fiber Post - Camila Ferreira Silva; Victor da Mota Martins; Anahi de Paula Melo; Laís Carvalho Martins; Paulo César Freitas Santos‐Filho (2020)
Abstract Objectives The aim of this study is to evaluate the influence of different composite resin in the customization of glass fiber posts (GFPs) on bond strength and failure mode. Materials and Methods Thirty bovine roots were selected. The wall roots were reduced so that each wall had a minimum dentin thickness of 1 mm. Thirty GFPs were divided into three groups (n = 10), which received different types of customization. The first had the GFP relined by bulk-fill flowable composite resin (BF), the second group had the GFP customized by conventional regular composite resin (CR), and the third group was cemented with dual resin cements (DRC), without relining. The root were sectioned, resulting in two 1.0-mm thick slices from cervical root regions only and push-out bond strength test was performed (EMIC, Universal testing machine). To determine failure mode, a stereomicroscope was used at ×40 magnification, with a 2.5D analysis. Statistical Analysis Data were analyzed using two-way ANOVA (α = 0.05) and Tukey’s test. Results BF (9.08 ± 1.9) and CR (9.17 ± 3.00) did not show a statistically significant difference (p = 0.961), regarding the bond strength test values. However, there was a statistically significant difference between DRC (5.44 ± 1.89) and the others (p < 0.05). BF (66.66%) and the CR group (47.61%) presented a predominantly failure mode type 6: mixed between resin cement and composite. While the highest failure index of the DRC group was type 2: adhesive between resin cement and dentin (47.61%). Conclusion BF can be an alternative for the customization of fiber posts, since it presented a similar behavior to the established technique with conventional composites.